2001
DOI: 10.1007/s004320000173
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and therapy of sporadic and familial medullary thyroid carcinoma

Abstract: Medullary thyroid carcinoma (MTC) is a rare thyroid malignancy. About 75% are sporadic (sMTC) while the remaining 25% are hereditary (hMTC). The treatment of choice for both sMTC and hMTC is surgery. An adequate initial operation provides the best chance of cure. Hence, the diagnosis of MTC should be made preoperatively. In sMTC, ultrasound, ultrasound-guided fine-needle aspiration cytology and measurement of calcitonin levels (basal and after injection of calcitonin-stimulating reagents, e.g., pentagastrin) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 50 publications
(64 reference statements)
2
30
0
4
Order By: Relevance
“…The patients with codon 634 mutations were associated with PHEO in 80% of cases and with PHPT in 40%. The prevalence of PHEO and PHPT in codon 634 mutations and the median age of patients at diagnosis are in accordance with published data [12,[23][24][25]. Most studies have focused on mutation Cys634Arg and its association with PHPT [21,24] The observed differences in the presence of PHEO and PHPT among mutations Cys634Arg, Cys634Gly and Cys634Tyr in our study were not confirmed in larger groups of patients [24].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The patients with codon 634 mutations were associated with PHEO in 80% of cases and with PHPT in 40%. The prevalence of PHEO and PHPT in codon 634 mutations and the median age of patients at diagnosis are in accordance with published data [12,[23][24][25]. Most studies have focused on mutation Cys634Arg and its association with PHPT [21,24] The observed differences in the presence of PHEO and PHPT among mutations Cys634Arg, Cys634Gly and Cys634Tyr in our study were not confirmed in larger groups of patients [24].…”
Section: Discussionsupporting
confidence: 77%
“…Genetic screening can provide information on these RET mutations in family members even before the earliest pathologic changes occur. Since individuals with RET proto-oncogene mutations have a 95% life-time risk of acquiring MTC [8], they are candidates for prophylactic thyroid surgery [3,9,10] Surgery is still the treatment of choice for MTC and the stage of the disease at diagnosis is the most important prognostic factor [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…TT has been regarded as the minimal surgical procedure for MTC patients and the recommended procedure consists of TT and at least lymphadenectomy of the cervicocentral compartment [4][5][6][7]. Lymphadenectomy extension of the other cervicomediastinal compartments is more controversial but is likely to determine the cure rate.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases can occur in more than 50% of cases at diagnosis [1][2][3]. Surgery is the only effective treatment [4][5][6][7]. There are no complementary approaches to surgery like 131 I for carcinomas of the follicular epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative provocative tests, such as calcium or omeprazole, have been reported, but the sensitivity and accuracy of those tests are not as good as pentagastrin [12,13]. Analysis of the germ line mutation of RET proto-oncogene is another alternative only applicable to hereditary MTC patients [14,15]. Re-examination of FNAC to inform the pathologist of the possibility of MTC is also worthwhile [16].…”
Section: Discussionmentioning
confidence: 99%